Differences in Coma Recovery Scale-Revised performance in an upright position versus lying position - DaCosta, Andrew; Fakhreddine, Aya Bou; Stroever, Stephanie; Stork, Ryan; O’Brien, Katherine; Zhang, Bei (Frontiers in Neurology, 2025)
The study investigated the impact of patient positioning on behavioral assessment of consciousness in individuals with a disorder of consciousness (DoC) using the Coma Recovery Scale-Revised (CRS-R). In this retrospective study, 1,470 CRS-R assessments were performed on 232 patients in four different positions: lying in bed (Bed), sitting at edge of mat (Mat), sitting in a wheelchair (Wheelchair), and standing (Standing), in an acute inpatient rehabilitation setting. A conditional random coefficients multi-level model was used to examine changes in the transformed CRS–R total unit (which converted the raw CRS-R total score to an equal-interval scale) across positions, accounting for repeated measurements within subjects and variability introduced by different raters. Transformed CRS–R total unit was significantly associated with assessment position. Compared to the Bed position (controlling age, gender, etiology, number of arousal protocol used, and days post-injury), patients assessed in the Wheelchair, Mat, and Standing positions had estimated 2.7-, 3.2-, and 3.5-unit increases in the transformed CRS–R total unit (p = 0.02, 0.01, and 0.11), respectively. Number of arousal protocols used was not significantly associated with assessment position. Increased use of these protocols did not enhance CRS–R performance. Improved physical and cognitive functionality in an upright position, rather than arousal alone, may contribute to the improvements on the CRS-R. Our results revealed that patients scored higher on the CRS-R in an upright position compared to a lying position. This suggests that the CRS-R is better performed in an upright position instead of a lying position in patients with DoC. We recommend assessing the level of consciousness in patients with DoC in an upright position and out of bed whenever feasible.